Abatisasi Selektif Dan Pemberantasan Sarang Nyamuk Serta Pendidikan Kesehatan Di Desa Batubulan Kecamatan Sukawati Kabupaten Gianyar Tahun 2019 - I Nyoman Gede Suyasa; Nengah Notes; I Wayan Sudiadnyana; Ni Ketut Rusminingsih (Poltekkes Kemenkes Denpasar, 2020)
Based on data from the public health center Sukawati II in the Gianyar District Health Office, there were 13 cases of DHF in Batubulan Village in 2017. Batubulan Village 13 cases with PR 0.10% ABJ of 92.9% with a population of 8,812 people. Community service aims to reduce the incidence of DHF in Batubulan Village after Selective Abatation, PSN and health education activities.The results of evaluation of community service activities obtained 494 containers from 130 houses examined, tested positive for Ae larvae. Aegypti as many as 20 containers with House Index (5.4%), Container Index (4.2%) and Bruteau Index (15.4%). The larvae free rate was 94.6%, it was categorized as having a high risk of transmission of DHF.It is expected that the community will continue to actively carry out activities to eradicate mosquito nests by draining, burying, closing and larvicidal activities as well as to health workers / cadres to carry out counseling about controlling DHF.Keywords: Selective Abatization and Eradication of Mosquito Hives